Biodiesel production using a novel heterogeneous catalyst, magnesium zirconate (Mg2Zr5O12): Process optimization through response surface methodology (RSM) - Singh V.; Belova L.; Singh B.; Sharma Y.C. (My University, 2025)
A heterogeneous catalyst, magnesium zirconate (Mg2Zr5O12) was synthesized by co-precipitation and was used for biodiesel production via transesterification. Kusum oil was used as a feedstock. Catalyst characterization was accomplished by TGA, XRD, ATR FTIR, SEM, and EDX. The parameters viz. particle size, zeta potential, BET surface area and basicity of the catalyst were also determined. Characterization of catalyst supports the formation of single phase Mg2Zr5O12 and the catalyst was able to catalyse the transesterification reaction for economically viable biodiesel production. Various reaction parameters such as molar ratio (methanol: oil), catalyst concentration and reaction time were optimized in presence of Mg2Zr5O12 by using Response Surface Methodology (RSM) based on Box-Behnken design. The catalyst was reusable up to seven runs with ∼75% conversion in the seventh run. Maximum conversion of 97.98% FAME was obtained at 18:1 M ratio (methanol: oil), 2.5 wt% of catalyst at 65 °C temperature for 150 min. Physicochemical properties of FAME were also studied as per ASTM standard method. © 2018